"And Yet It Moves": Dream and Reality of the Ecumenical Movement: Reflections on the 11th Assembly of the World Council of Churches in Karlsruhe. Issue 1 (7th April 2023) - Werner, Dietrich
Abstract: This article offers an overview of the 11th Assembly of the World Council of Churches, which met in Karlsruhe, Germany, in August–September 2022. It sets out the context in which the assembly took place, the main issues discussed, and perspectives for the future. The article argues that the assembly in Karlsruhe demonstrated that the ecumenical movement still is alive and can offer enormous potential in a world at the brink of a new East–West divide, facing a significant weakening of multilateral structures of cooperation, and even the threat of nuclear war. Moreover, the Karlsruhe assembly demonstrated that on subjects such as the Middle East, peace ethics, and nationalism, and in the deep commitment and spiritual life of its participants, the ecumenical movement is vital and vibrant and represents a countercultural force against rigid nationalisms.